RECONCEPTUALIZING LISTENING IN TASK-BASED LANGUAGE TEACHING: FROM PASSIVE RECEPTION TO ACTIVE UNDERSTANDING - Mardona Rakhimova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Introduction Listening has traditionally been viewed as a passive, receptive skill in language education.  In  many  classrooms,  learners  listen  to  recordings  and  answer comprehension questions, with success measured by the number of correct responses. Such practices often reduce listening to a testing activity rather than recognizing it as a dynamic cognitive process. However, contemporary approaches to second language acquisition suggest that listening should be understood as active meaning construction. Task-Based  Language  Teaching  (TBLT)  provides  a  framework  for  this reconceptualization. Instead of treating listening as isolated input, TBLT embeds it within  meaningful  tasks  that  require  learners  to  achieve  specific  communicative outcomes. This paper argues that listening should move from passive reception toward active understanding through task-based pedagogy. The discussion explores theoretical foundations,  cognitive  dimensions,  pedagogical  applications,  and  implications  for academic and professional contexts.